How do smart city pilots affect the ESG performance of manufacturing firms? evidence from China - Tang, Haisheng; Wang, Jeng-Bang; Ou, Chung-Ya (Frontiers in Environmental Science, 2024)
The literature has extensively presented analysis of the factors influencing environmental, social, and governance (ESG) performance, but scant studies have delved into the interplay between smart cities and said performance. This oversight is surprising, given the pivotal role governments in developing countries play in spearheading smart city initiatives. As the influence of smart city pilot (SCP) policy, orchestrated by governments, on the ESG performance of manufacturing firms remains unverified, our study takes SCP as a quasi-experiment to probe the effects of smart city development on this performance. Taking data from 2,229 listed manufacturing firms in China spanning from 2009 to 2020, our findings reveal that SCP markedly elevates their ESG performance. Detailed heterogeneity analysis indicates that the positive impact of SCP on performance predominantly benefits non-state-owned enterprises. Regionally, SCP significantly boosts corporate ESG performance in eastern and central China, though its effects are muted in the west region. Two key mechanisms through which SCP augments corporate ESG performance are fostering green innovation investment and refining internal control quality. This paper offers valuable insights for policymakers and business leaders in China and other emerging economies, guiding them towards bolstering ESG performance and realizing sustainable corporate growth.